(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The (PVA-PVP- CdS) composites were made with different weight percentages of Cadmium sulfide particles as a filler. All samples were prepared as films by solution casting way. The experimental outcomes show that the dielectric constant increase with rising of the frequency of applied electrical field and concentration of the filler. Dielectric loss decreases with the increasing the frequency while it increased with the increases of concentration of the Cadmium sulfide. The A.C electrical conductivity increases with increasing the filler and frequency for the (PVA-PVP- CdS) composites